The potential of expanded noninvasive prenatal screening for detection of microdeletion and microduplication syndromes. (3rd July 2021) - Shi, Panlai; Wang, Yuan; Liang, Hongbin; Hou, Yaqin; Chen, Duo; Zhao, Ganye; Dai, Peng; Xia, Yanjie; Feng, Yin; Cram, David S.; Kong, Xiangdong
Abstract: Objectives: To evaluate the clinical potential of a higher resolution noninvasive prenatal screening (NIPS‐Plus) test for detection of microdeletion/microduplication syndromes (MMS) in addition to common aneuploidies. Methods: In a multicenter prospective study, 37, 002 pregnant women with unremarkable first‐trimester ultrasound scans had a NIPS‐Plus test. Ultrasound screen positive women were not included in this study. Results: Of 36, 970 ultrasound negative women there were 291 NIPS‐Plus screen positive results indicating 237 aneuploidies and 54 MMS. Following amniocentesis, 171 (72%) were confirmed as genuine, comprising 3 T13s, 10 T18s, 61 T21s, 70 SCAs and 27 MMS. The PPV for MMS with unremarkable ultrasound findings was 50%. Routine clinical examination of children born from NIPS‐Plus negative pregnancies revealed no obvious signs of chromosome disease syndromes at one year of age. Conclusions: NIPS‐Plus has the potential for clinical utility not only for routine aneuploid screening but also for MMS that do not show overt signs during early pregnancy ultrasound screening. We suggest that ultrasound with NIPS‐Plus in combination with appropriate counselling could be considered as a comprehensive first‐tier prenatal screening approach for all pregnant women. Key points: What's already known about this topic? First trimester screening (biochemistry plus ultrasound) have high risk screening rates for major trisomies approaching 5% of pregnancies most of which are false positive. Similarly, ultrasound and NIPS has some detection ability for MMS but is limited. Current noninvasive prenatal screening (NIPS) tests exhibit variable positive predictive values (PPVs, 11%‐77%) for detection of MMS. What does this study add? Our high resolution NIPS‐Plus test extended the range of noninvasive prenatal testing with opportunity to detect MMS in unremarkable ultrasound pregnancies. The combination of ultrasound and NIPS‐Plus provides the opportunity to improve identification of clinically significant chromosome aberrations and so increase the confidence for a better informed decision for all couples undergoing prenatal assessments.